CHIMBRIDS - chimeras and hybrids in comparative European and international research: scientific, ethical, philosophical and legal aspects - Taupitz, Jochen; Weschka, Marion (Springer-Verlag Berlin Heidelberg, 2009)
National, European and international concepts and strategies concerning the legal and ethical framework of chimera and hybrid research are still largely missing, even though they are absolutely necessary in order to use the potential of chimera and hybrid research effectively and efficiently for the benefit of science and society. The outcome of the CHIMBRIDS-Project successfully sheds light on the chances and risks of this research and provides legal solutions to existing problems in order to help decision-makers fulfil their tasks in an informed and efficient manner. This comprehensive volume details the complete results, contributed by 40 scholars from 10 member states of the European Union, Canada, China, Israel, Japan, Switzerland and the US, with descriptive reports of the legal situation in specific countries and in-depth analysis of all scientific, medical, ethical and legal implications of chimera and hybrid research.
Includes bibliographical references and index
Keywords: Recht; Medizinische Ethik; Tiere; Hybride; Mensch; Europäische Union; Chimäre